Ectopic parathyroid adenoma in the submandibular region: a case report. Issue 10 (December 2019) - Kong, Y.; Ge, S.Y.; Shang, W.; Song, K.
Abstract: Ectopic parathyroid adenomas that affect the submandibular region have not been widely reported. We describe a 34-year-old man who presented with a painless swelling of the submandibular region. The identification of hypercalcaemia encouraged us to engage a multidisciplinary team to evaluate further serum changes. Parathyroid hormone analysis, 99m Tc-methoxy-isobutyl-isonitrile ( 99m Tc-MIBI) scintigraphy, and single-photon emission computed tomography (SPECT-CT) were done to rule out hyperparathyroidism. Raised parathyroid hormone together with 99m Tc-MIBI and SPECT-CT examination were consistent with a tumour caused by the hyperparathyroidism. Removal of the lesion resulted in rapid improvement in serum calcium and parathyroid hormone, and the normalisation of the serum creatinine, concentrations. Histopathological analysis confirmed a parathyroid adenoma. We conclude that ectopic parathyroid adenomas should be considered as part of a differential diagnosis for tumours of the submandibular region.